Advanced transient switching and coordinated power control strategies for flexible interconnection of multiple microgrids - Li, Guoliang; Lin, Xia; Kong, Lingyuan; Xia, Wenhua; Yan, Shuang (Frontiers in Energy Research, 2024)
The multi-microgrid distribution system faces challenges due to variations in individual microgrid operational status, resulting in voltage and current fluctuations during transient interconnection. The impedance of interconnecting lines further exacerbates uneven power distribution among microgrids, threatening the operational stability of the system. To achieve flexible and seamless interconnection between multiple microgrids (MGs), the paper fully analyzes the interconnection structure and operation mode of microgrids, and then designs a transient switching control method to ensure smooth transition of MGs based on the investigations of the transient interconnection process. Additionally, to balance the power distribution among interconnected microgrids, a voltage-current-based power coordinated control strategy is also synthesized, taking advantage of the advanced synchronized fixed-frequency technology. Simulation case studies are carried out. Results indicate that the proposed power coordinated control effectively facilitates instantaneous interconnection between isolated regions, avoiding voltage disturbances and current surges. Furthermore, it efficiently equalizes and distributes output power from distributed energy sources, thereby enhancing the operational flexibility and stability of the MGs and distribution system.